PENENTUAN RETENSI OPTIMAL DAN HARGA PREMI DARI ASURANSI KE REASURANSI DENGAN VALUE AT RISK - , DIAN SARASWATI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The general Insurance must take over the loss risk of the item which is insured by policy holder. The loss risk can be high, can be low. The general Insurance will face a problem if the loss risk are high, in this case, means that the fund are used to pay the claim are high. And the solution is by reinsure the policy in reinsurance company. Its means that the insurance will share the risk with the reinsurance. The Insurance have to pay amount of fund periodically which is called premium reinsurance. The reinsurance must take over some of the loss risk. The general Insurance determine the retention of the loss risk by optimation of the value at risk. The resulting optimal solution of optimation criterion has several important characteristics, such as: the optimal retention has a very simple analytic form